2013
DOI: 10.1007/s00122-013-2227-1
|View full text |Cite
|
Sign up to set email alerts
|

Determination of heterotic groups for tropical Indica hybrid rice germplasm

Abstract: Two heterotic groups and four heterotic patterns were identified for IRRI hybrid rice germplasm to develop hybrid rice in the tropics based on SSR molecular data and field trials. Information on heterotic groups and patterns is a fundamental prerequisite for hybrid crop breeding; however, no such clear information is available for tropical hybrid rice breeding after more than 30 years of hybrid rice commercialization. Based on a study of genetic diversity using molecular markers, 18 parents representing hybrid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
48
1
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 64 publications
(53 citation statements)
references
References 22 publications
3
48
1
1
Order By: Relevance
“…Taking this new classification into consideration, breeders will be able to use the genetic diversity available to create mating schemes for determining the heterotic performance of hybrids by assessing marker-based parental groups. This type of experimental design could be of interest for field traits such as yield and disease resistance (Xie et al 2014). However, quality traits could also be managed by this type of study since the biochemical composition throughout the genetic groups is highly variable, especially for caffeine and chlorogenic acids (Ky et al 2001;Campa et al 2004).…”
Section: Qtl Detection On Coffee In the Literaturementioning
confidence: 99%
“…Taking this new classification into consideration, breeders will be able to use the genetic diversity available to create mating schemes for determining the heterotic performance of hybrids by assessing marker-based parental groups. This type of experimental design could be of interest for field traits such as yield and disease resistance (Xie et al 2014). However, quality traits could also be managed by this type of study since the biochemical composition throughout the genetic groups is highly variable, especially for caffeine and chlorogenic acids (Ky et al 2001;Campa et al 2004).…”
Section: Qtl Detection On Coffee In the Literaturementioning
confidence: 99%
“…Conventionally, genetic variances of the targeted populations, per se performance and adaptation of the parental lines and the ratio of general combining ability (GCA) to specific combining ability (SCA) have been used to identify heterotic groups (Melchinger, 1999) and the methods have been used in in a number of crops such as triticale and maize (Reif et al, 2005). Molecular markers based genetic distance have also been used to identify heterotic groups in a number of crops including rice (Xie et al, 2014) and triticale . Well established heterotic groups have been developed for maize mainly for the temperate environments (Tracy and Chandler, 2006).…”
Section: Exploitation Of Heterosismentioning
confidence: 99%
“…Both per se performance and combining ability of the inbred parents have been used separately or in combination to predict hybrid performance for different crops including sorghum (Mahama et al, 2014;Kenga et al, 2006); maize (Kebede et al, 2013;Makanda et al, 2010) and rice (Xie et al, 2014). The aforementioned studies have reported positive correlations between inbred per se performance and their hybrid grain yield performance under both drought stress and non-stressed conditions in subtropical and tropical environments.…”
Section: Per Se Performance and Combining Ability Of Inbred Parentsmentioning
confidence: 99%
See 2 more Smart Citations